Vertical Segregation and Phylogenetic Characterization of Ammonia-Oxidizing Bacteria and Archaea in the Sediment of a Freshwater Aquaculture Pond - Lu, Shimin; Liu, Xingguo; Ma, Zhuojun; Liu, Qigen; Wu, Zongfan; Zeng, Xianlei; Shi, Xu; Gu, Zhaojun (Frontiers in Microbiology, 2016)
Pond aquaculture is the major freshwater aquaculture method in China. Ammonia-oxidizing communities inhabiting pond sediments play an important role in controlling culture water quality. However, the distribution and activities of ammonia-oxidizing microbial communities along sediment profiles are poorly understood in this specific environment. Vertical variations in the abundance, transcription, potential ammonia oxidizing rate, and community composition of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) in sediment samples (0–50 cm depth) collected from a freshwater aquaculture pond were investigated. The concentrations of the AOA amoA gene were higher than those of the AOB by an order of magnitude, which suggested that AOA, as opposed to AOB, were the numerically predominant ammonia-oxidizing organisms in the surface sediment. This could be attributed to the fact that AOA are more resistant to low levels of dissolved oxygen. However, the concentrations of the AOB amoA mRNA were higher than those of the AOA by 2.5–39.9-fold in surface sediments (0–10 cm depth), which suggests that the oxidation of ammonia was mainly performed by AOB in the surface sediments, and by AOA in the deeper sediments, where only AOA could be detected. Clone libraries of AOA and AOB amoA sequences indicated that the diversity of AOA and AOB decreased with increasing depth. The AOB community consisted of two groups: the Nitrosospira and Nitrosomonas clusters, and Nitrosomonas were predominant in the freshwater pond sediment. All AOA amoA gene sequences in the 0–2 cm deep sediment were grouped into the Nitrososphaera cluster, while other AOA sequences in deeper sediments (10–15 and 20–25 cm depths) were grouped into the Nitrosopumilus cluster.